Heat and dust - Jhabvala, Ruth Prawer, 1927-2013. (New York : Simon & Schuster, 1987)
Set in India, HEAT AND DUST is the story of Olivia, a beautiful, spoiled, bored English colonial wife in the 1920s who is drawn inexorably into the spell of the Nawab, a minor Indian prince deeply involved in plots and intrigues. Olivia outrages the tiny, suffocating town where her husband is a civil servant by eloping with the captivating Nawab. It is also the story of Olivia's step-granddaughter who, fifty years later, is drawn to India by her fascination with the letters left behind by the now dead older woman, and by her obsession with solving the enigma of Olivia's scandal. A penetrating and compassionate love story, this brilliant novel immerses the reader in the heat, dust, and squalor of India, while providing a compelling mixture of the spiritual and the sensual.
"A Fireside book."
Keywords: British -- India -- Fiction; Married women -- Fiction; India -- History -- British occupation, 1765-1947 -- Fiction; India -- Kings and rulers -- Fiction; Historical fiction